Understanding Lifestyle Disorders in Shalakya Tantra with an Ayurvedic Approach (AYUSHDHARA, 2025)
Lifestyle is influenced by personal choices, cultural background, socioeconomic status, and environmental factors, and it plays a significant role in shaping overall quality of life. Now days every person is running after life's goal Hence does not have time to think and act healthy life, they are not able to follow exercise, dietetic rules and regulations which lead to the lifestyle disorders. Present lifestyle and environmental pollution are causing hazardous effects on health. Likewise, disorders associated with the way a person or group of people live is called as lifestyle disorders. Shalakya Tantra is one of the eight branches of Ayurveda, the traditional system of medicine in India. It primarily deals with the diagnosis, treatment, and prevention of diseases related to the upper parts of the body. It focuses on ear, nose, throat, head disorders and ophthalmology (eye care). In this article we will discuss the Shalakya Tantra and role of lifestyle disorders related to Shalakya Tantra.